Association between cardiovascular risk factors and atrial fibrillation - Wu, Guohao; Wu, Jingguo; Lu, Qin; Cheng, Yunjiu; Mei, Weiyi (Frontiers in Cardiovascular Medicine, 2023)
Background The most prevalent sustained arrhythmia in medical practice, atrial fibrillation (AF) is closely associated with a high risk of cardiovascular disease. Nevertheless, the risk of AF associated with cardiovascular risk factors has not been well elucidated. We pooled all published studies to provide a better depiction of the relationship among cardiovascular risk factors with AF. Methods Studies were searched in the MEDLINE, Web of Science, and EMBASE databases since initiation until January 15, 2022. Prospective cohort studies assessing the relationship a minimum of single cardiovascular risk factors to AF incidence were included if they contained adequate data for obtaining relative risks (RR) and 95% confidence intervals (CI). Random-effects models were utilized to perform independent meta-analyses on each cardiovascular risk factor. PROSPERO registry number: CRD42022310882. Results A total of 17,098,955 individuals and 738,843 incident cases were reported for data from 101 studies included in the analysis. In all, the risk of AF was 1.39 (95% CI, 1.30–1.49) for obesity, 1.27 (95% CI, 1.22–1.32) per 5 kg/m2 for increase in body mass index, 1.19 (95% CI, 1.10–1.28) for former smokers, 1.23 (95% CI, 1.09–1.38) for current smokers, 1.31 (95% CI, 1.23–1.39) for diabetes mellitus, 1.68 (95% CI, 1.51–1.87) for hypertension, and 1.12 (95% CI, 0.95–1.32) for dyslipidemia. Interpretation Adverse cardiovascular risk factors correlate with an increased risk of AF, yet dyslipidemia does not increase the risk of AF in the general population, potentially providing new insights for AF screening strategies among patients with these risk factors. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/, PROSPERO identifier (CRD42022310882).